A Qualitative Study of the Psychological Empowerment of Women with a Healthy Adult Mode - Mahmoodinejad, Hamidreza; Dayarian, Mohammad Masood; Mousavi, Ismail (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The Healthy Adult mode is one of the primary modes in schema therapy, reflecting maturity, mental health, and good judgment. The present study aimed to qualitatively investigate the psychological empowerment of women with a Healthy Adult mode. Methods: This qualitative study was conducted using a phenomenological approach. Participants included women aged 20-40 from Isfahan Province in 2023, selected through purposive sampling based on inclusion criteria. Data were examined using semi-structured, in-depth interviews. Data saturation was achieved with 20 interviews. Data were analyzed using Colaizzi’s seven-step method. Findings: After interviewing women with a Healthy Adult mode and analyzing the data, 80 initial codes, 8 sub-themes, and 2 main themes were extracted. Coping and self-awareness were classified under the main themes, and self-compassion, self-regulation, problem-solving ability, mindfulness, developed social relationships, assertiveness, self-awareness, and the concept of a "good enough" parent were classified under the sub-themes. Conclusion: Based on the findings of this study, it can be concluded that Iranian women with a Healthy Adult mode have developed components of psychological empowerment. Ultimately, it is suggested that counseling centers and organizations use practical services based on the findings of this research to enhance the psychological empowerment and promote the adult state of personality in women.